Objective and subjective knowledge of HIV/AIDS as predictor of condom use in adolescents - Villaseñor-Sierra, Alberto; Caballero-Hoyos, Ramiro; Hidalgo-San Martín, Alfredo; Santos-Preciado, José Ignacio (Salud pública de México, 2003)
To evaluate the association between objective and subjective knowledge on HIV/AIDS and condom use. Analysis of a database from an anonymous, self-applied, randomized survey conducted between 1995 and 1996. Study subjects were 1,410 adolescents of four socioeconomic strata from Guadalajara, Mexico. Objective knowledge was assessed with 24 questions regarding HIV/AIDS, and subjective knowledge with the question "how much do you think you know about HIV/AIDS?" The variables associated with condom use were identified using logistic regression analysis and by calculating odds ratios with a 95% confidence interval. The degree of objective knowledge was "average", differentiated by socioeconomic strata (p < 0.001), and was higher in adolescents from medium and high socioeconomic strata (p < 0.008). Regarding subjective knowledge, adolescents from the low, medium, and high socioeconomic strata claimed to know "a little", and the ones from the lowest stratum claimed to know "very little". Condom use was higher in males (35.4%), and in adolescents from high socioeconomic strata (p < 0.005), than in females (15.3%) (p < 0.001). Although there was a correlation between objective and subjective knowledge (r = 0.37, p < 0.001), a higher degree of subjective knowledge was associated with condom use (p < 0.001). Subjective knowledge, belonging to medium and high socioeconomic strata and being male, were predictors of condom use.